Dihydrophytol and phytol isomers as marker substances for hydrogenated and refined vegetable oils - Schröder, Markus; Lehnert, Katja; Hammann, Simon; Vetter, Walter (European Journal of Lipid Science and Technology, 2014)
Edible vegetable oils are an important part of the human diet. Products with different levels of processing are marketed for this purpose. Key‐products are virgin oils, refined oils, and partly or fully hydrogenated oils. In this study we explored whether compounds derived from trans‐phytol, i.e. the natural constituent of chlorophyll, could serve as marker compounds for identifying the processing type of oils, spreads and margarines. The evaluation was based on the contribution of the native trans‐phytol along with its transformation products cis‐ and iso‐phytol as well as dihydrophytol. Gas chromatography with mass spectrometry operated in the selected ion monitoring mode enabled the detection of these compounds at >0.01 mg/100 g oil or fat. In virgin vegetable oils trans‐phytol was the principle phytol related compound while cis‐phytol was generally <0.05% and iso‐phytol and dihydrophytol were not detected at all. Refined vegetable oils contained trans‐, cis‐, and iso‐phytol but no dihydrophytol. Partly and totally hydrogenated vegetable oils contained dihydrophytol if at least 5% hydrogenated fat were present in the oil. The occurrence of cis‐ and iso‐phytol in vegetable oils can be used as indicators for refined oils while the presence of dihydrophytol in vegetable oils is an indication for hydrogenation. Practical applications: The analysis of trans‐phytol, cis‐phytol, iso‐phytol, and dihydrophytol can be used in food control for oil authentication. In this context iso‐phytol can serve as an additional marker for refined vegetable oils and dihydrophytol as a marker for hydrogenated vegetable oils.
Keywords: Dihydrophytol; Authentication; Phytol; Hydrogenated oils; Virgin oils; Refined oils